Developing Biomedical Devices Design, Innovation and Protection - Andreoni, Giuseppe; Barbieri, Massimo; Colombo, Barbara; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
During the past two decades incredible progress has been achieved in the instruments and devices used in the biomedical field. This progress stems from continuous scientific research that has taken advantage of many findings and advances in technology made available by universities and industry. Innovation is the key word, and in this context legal protection and intellectual property rights (IPR) are of crucial importance. This book provides students and practitioners with the fundamentals for designing biomedical devices and explains basic design principles. Furthermore, as an aid to the development of devices and products for healthcare, it presents a brief description of the human body, covering anatomy and physiology, that will assist the reader in understanding the origin of biosignals, their significance, and the technology to be used in their measurement. Issues concerning IPR and protections are also fully discussed, with examples and opportunities for IPR exploitation.
Introduction -- Emerging issues in healthcare -- Innovation demand -- Innovation process and methods -- Innovation and Rights -- Intellectual Property Rights: terms, definitions -- Prior art and analysis of innovation -- What models for patenting -- What to do after the patent: transfer, licensing, spin-off, start-up -- Examples -- Case study -- Wearable systems and related IPR.
Keywords: Engineering; Engineering design; Biomedical engineering; Engineering; Biomedical Engineering; Engineering Design; International IT and Media Law, Intellectual Property Law